The Synergy of Religion and Malay Culture in Improving the Empowerment of Islamic Communities Towards Achieving SDGS - Aldi, Muhammad; Khairanis, Retisfa (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
Many Malay Muslims face challenges related to social and economic development in pursuit of the Sustainable Development Goals (SDGs), especially those related to social justice and poverty. Conversely, the synergy between Islam and Malay customs has untapped potential in helping the general public to achieve the SDGs. The objectives of this study are to (1) examine how integrating Islam and Malaysian culture can improve the well-being of the general public, (2) identify factors that contribute to this collaboration in relation to poverty and well-being (SDG 1 and SDG 10), and (3) investigate the contribution of Islam and Malaysian culture in the development of an inclusive society (SDG 11 and SDG 16). The method used was descriptive qualitative, interview data collection using religious and secular texts, participatory observation, and document analysis. Data analysis was done thematically to identify factors that contribute to the well-being of the general public. The results showed that the synergy between Islam and Malay culture is crucial in enhancing social solidarity, poverty alleviation, and community development. The strong application of religious values and customs is proven to promote the achievement of SDGs at the local level and strengthen social cohesion. Keyword : Islam, Malay Culture, SDGs